Comissionamento e dosimetria de TBI utilizando filme radiocrômico, câmara de ionização e detector OSL - Marins, Priscila de França (2019)
The total body irradiation (total body irradiation - TBI) is a special technique of radiotherapy that is part of the bone marrow transplantation conditioning to treat patients with leukemia, lymphoma, autoimmune diseases, multiple myeloma, among others. The measure of this procedure is immunosuppression, bone marrow ablation and destruction of malignant cells, in order to prevent the medication of the transplanted patient. Doses will be considered equivalent or higher for tolerance of risks. This issue is related to dosimetry, a procedure in which it is possible to verify delivery of the dose to the surface or internal organs. Thus, in this study was a methodological unit for the commissioning, consisting of the assessment of the deepdose distribution of the primary problem (PDP) and the off-axis factor for linear accelerator used in the TBI procedures radiocromatic films. After commissioning, the dosimetry parameters were evaluated by means of the internal time dose of an anthropomorphic phantom connected to radiological films and OSO detectors of BeO. As light plates, they were linearly linear, with a capacity of 20 cm depth, radiological films and an ionization chamber were used inside a cubic ghost with water. Positioning the radiochromic film, within a continuous image card phantom at depths of 1.5 to 15 cm for 6 VM and depths of 2.5 to 15 cm for 15 MV, it was possible to calculate the offaxis factor of the central center (dose in the air) The ionization chamber and the radiometric films show the PDPs (differences of up to 5%) In addition, the BeO OSL detectors and the radiometallic films obtained, on average, similar results, to the value In this way, it is concluded that the radiological studies are advantageous for the performance of linear tests and can facilitate and improve the measurement of the indicator dosimeters. BeO detectors can be used for in vivo evaluation during the TBI process.